2022
DOI: 10.1021/acs.inorgchem.2c03015
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Binuclear Ir(III)–Cu(II) Coordination Compounds with Phosphino-Fluoroquinolone Conjugates for Human Prostate Carcinoma Treatment

Abstract: Novel heteronuclear Ir III −Cu II coordination compounds ([Ir(η 5 -Cp*)Cl 2 Pcfx-Cu(phen)](NO 3 )•1.75(CH 3 OH)•0.75(H 2 O) (1), [Ir(η 5 -Cp*)Cl 2 Pnfx-Cu(phen)](NO 3 )•1.75(CH 3 OH) 4)) bearing phosphines derived from fluoroquinolones, namely, sparfloxacin (Hsfx), ciprofloxacin (Hcfx), lomefloxacin (Hlfx), and norfloxacin (Hnfx), have been synthesized and studied as possible anticancer chemotherapeutics. All compounds have been characterized by electrospray ionization mass spectrometry (ESI-MS), a number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…3D cultures are being used to develop novel carrier systems with the possibility to penetrate deeper into the structure of the tumor and deliver specific compounds, such as radionuclides, miRNA, and drugs. Several carriers have been tested that have shown increased permeability, even in 3D cultures [ 107 , 121 , 126 , 141 , 142 , 179 , 180 ].…”
Section: Standard and Novel Therapies Used In 3d Models Of Pcmentioning
confidence: 99%
“…3D cultures are being used to develop novel carrier systems with the possibility to penetrate deeper into the structure of the tumor and deliver specific compounds, such as radionuclides, miRNA, and drugs. Several carriers have been tested that have shown increased permeability, even in 3D cultures [ 107 , 121 , 126 , 141 , 142 , 179 , 180 ].…”
Section: Standard and Novel Therapies Used In 3d Models Of Pcmentioning
confidence: 99%
“…Significant differences between the permeation and destination of luminescent probes between 2D and 3D cellular models have been reported . Therefore, in assessing potential PS sensitizers, permeation through 3D models should ideally also be considered but rarely have been to date in metal complex species, with only a small number of studies reported to date assessing metal complex PSs in spheroids. , A recent work includes lysosomal localizing Ru (II) complexes, studied by the Chao group in HeLa spheroids for two photon PDT, irradiating the spheroids at 10 J/cm 2 at 800 nm, and also the study of photoactive iridium (III) complexes in A549 spheroids by the Sadler group. , …”
Section: Introductionmentioning
confidence: 99%
“…50 Therefore, in assessing potential PS sensitizers, permeation through 3D models should ideally also be considered but rarely have been to date in metal complex species, with only a small number of studies reported to date assessing metal complex PSs in spheroids. 51,52 A recent work includes lysosomal localizing Ru (II) complexes, studied by the Chao group in HeLa spheroids for two photon PDT, irradiating the spheroids at 10 J/cm 2 at 800 nm, and also the study of photoactive iridium (III) complexes in A549 spheroids by the Sadler group. 53,54 Herein, we report on the application of tridentate coordinated [Ru(bqp)(bqpCOOEt)] 2+ (Ru-bqp-ester), where bqp = 2,6-bi(quinolin-8-yl)pyridine, and its peptide conjugates [Ru(bqp)(bqpCONH-ahx-FrFKFrFK(Ac)-CONH 2 )] 5+ (Ru- The parent complex (Figure 1), was selected as, when first reported by Hammarstrom et al, it showed an exceptionally long lived 3 MLCT excited state facilitated by the expanded coordination bite angle of the 2,6-bi(quinolin-8-yl)pyridine ligand so that the coordination geometry around the metal center is approximately octahedra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[30][31][32] The above-mentioned different mechanisms of action, ligand substitution kinetics, and various oxidation states contributed to potential redox activity, lower toxic effect, and higher cellular uptake efficiency give advantages to ruthenium and iridium complexes over platinum-based compounds. [33][34][35] Currently, two piano-stool ruthenium(II) complexes Ru(η 6 -pcymene)Cl 2 PPh 2 CH 2 OH (RuPOH) and Ru(η 6 -p-cymene)Cl 2 P(p-OCH 3 Ph) 2 CH 2 OH (RuMPOH) and two half-sandwich iridium(III) complexes Ir(η 5 -Cp*)Cl 2 PPh 2 CH 2 OH (IrPOH) and Ir(η 5 -Cp*)Cl 2 P(p-OCH 3 Ph) 2 CH 2 OH (IrMPOH) have been synthesized, physiochemically characterized and evaluated in vitro in terms of their potential anticancer activity in our research groups. [36] We concluded that all the studied complexes undergo slow hydrolysis and the complexes with the methoxy group on the phenyl rings can catalyze the oxidation of NADH to NAD + with higher efficiency than complexes without this group.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, triphenylphosphine can intercalate between DNA base pairs which increases anticancer activity [30–32] . The above‐mentioned different mechanisms of action, ligand substitution kinetics, and various oxidation states contributed to potential redox activity, lower toxic effect, and higher cellular uptake efficiency give advantages to ruthenium and iridium complexes over platinum‐based compounds [33–35] …”
Section: Introductionmentioning
confidence: 99%